Analisis Penerapan Tes UKBI Terhadap Kemampuan Mahasiswa Menulis Proposal Penelitian Dan Proposal Kegiatan - Rahel Veronika; Fitriani Lubis; Nurlia Aprianti; Daniel Sanggam; Dafa Ariza; Dwi Nabila (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to understand how students' ability to write good and quality research proposals and activity proposals. The data analysis technique used is descriptive analysis technique. The data collection method used for this research is the distribution of questionnaires to students at various universities in Indonesia with a population of 23 respondents and by conducting scientific searches with literature studies. The UKBI test is an objective means of evaluating the level of language mastery, including aspects of spelling and grammar. Participation in the UKBI Test can provide valuable feedback to students on the extent to which their abilities are in accordance with the prevailing Indonesian language standards.